The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s10534-012-9537-7
|View full text |Cite
|
Sign up to set email alerts
|

A case of multiple sclerosis improvement following removal of heavy metal intoxication

Abstract: Multiple sclerosis (MS) is a chronic progressive disease of the central nervous system (CNS) provoking disability and neurological symptoms. The exact causes of SM are unknown, even if it is characterized by focal inflammatory lesions in CNS accompanied by autoimmune reaction against myelin. Indeed, many drugs able to modulate the immune response of patients have been used to treat MS. More recently, toxic metals have been proposed as possible causes of neurodegenerative diseases. The objective of this study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 38 publications
(38 reference statements)
1
16
0
Order By: Relevance
“…We have previously studied the case of a young man affected by MS, who has been unsuccessfully treated for some years with current therapies [29]. Symptoms revealed by the patient were subacute vision loss, diplopia, and pain with eye movements as the first symptoms of optic neuritis; disturbance of fine motor skills; paresthesia and gait ataxia; bladder dysfunction; and significant tiredness.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously studied the case of a young man affected by MS, who has been unsuccessfully treated for some years with current therapies [29]. Symptoms revealed by the patient were subacute vision loss, diplopia, and pain with eye movements as the first symptoms of optic neuritis; disturbance of fine motor skills; paresthesia and gait ataxia; bladder dysfunction; and significant tiredness.…”
Section: Discussionmentioning
confidence: 99%
“…A study on patients with MS showed that the level of toxic metal in urine reduces after chelation therapies. [1973] Furthermore, chelation therapy can reduce lipid peroxidation and oxidative DNA damage. [69]…”
Section: Complementary and Alternative Medicinementioning
confidence: 99%
“…Urine collection following chelation treatment lasted 12 hours. Urine samples are accurately enveloped in sterile vials and sent to the Laboratory of Toxicology (Doctor's Data Inc., St. Charles, IL, USA) to be analysed, as previously reported [12]. Briefly, samples are acid-digested with certified metal-free acids (digestion takes place in a closed-vessel microwave digestion system), diluted with ultrapure water, and carried out via inductively coupled plasma with mass spectrometry (ICP-MS) utilizing collision/reaction cell methods coupled with ion-molecule chemistry, a reliable new method for reducing interference.…”
Section: Methodsmentioning
confidence: 99%
“…Two groups of subjects were studied: 39 patients affected and 11 subjects unaffected by ND (controls). All subjects were affected by chronic body burden of heavy metals and were treated with EDTA to remove metal intoxication [1214]. The subjects were also daily treated with antioxidant therapy to help the detoxification process: some of them received Cellfood and some other antioxidants [15].…”
Section: Introductionmentioning
confidence: 99%